Engineered Mutation of Some Important Amino Acids in Angiotensin II Type 1 (AT1) Receptor Increases the Binding Affinity of AT1-Receptor Antagonists - Mohiuddin Ahmed Bhuiyan; Murad Hossain; Masaji Ishiguro; Takashi Nakamura; Takafumi Nagatomo (Elsevier, 2010)
The present study was designed to examine the binding affinity and functional potency of selective angiotensin II type 1 (AT1)-receptor antagonists towards specific mutants of AT1 receptor using site-directed mutagenesis. We also compared our results with the wild-type AT1 receptor and investigated the possible reasons behind that. Both wild-type and mutant receptors were expressed in COS-7 cells and the binding affinities of the antagonists were determined by radioligand binding assay. Inhibition of agonist-stimulated inositol phosphate accumulation by the antagonists was also done. Substitution of asparagine235 of intracellular loop 3 of the AT1 receptor by arginine increased the binding affinity of the antagonists 5 - 34-fold, whereas the increase in the binding affinity of the antagonists in the phenylalanine239 mutant by arginine and tryptophan (F239R and F239W) were 3 - 19-fold and 2 - 15-fold higher, respectively, compared to the wild-type AT1 receptor. The results suggested that substitution by a positively charged or sterically hindered amino acid in the AT1 receptor allows it to interact with the acidic tetrazole moiety and carboxylate groups of the antagonists more strongly compared to the wild-type receptor. These findings may play an important role to change the binding affinity of the antagonists to an effective level for the pharmacological function of the drugs. Keywords:: site-directed mutagenesis, angiotensin II type 1 (AT1) receptor, radioligand binding, binding affinity, antagonist